Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26630/jak.v9i1.2112
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Faktor Suhu dan Kelembaban Dengan Kasus Demam Berdarah Dengue (DBD) di Kota Bandar Lampung

Abstract: Demam Berdarah <em>Dengue</em> (DBD) merupakan penyakit tular vektor pada manusia yang disebabkan oleh virus <em>dengue</em>  (DENV) dan disebarkan oleh nyamuk <em>Aedes aegypti</em> sebagai vektor utama<em>. </em>Kasus DBD di kota Bandar Lampung cenderung meningkat serta berpotensi menimbulkan Kejadian Luar Biasa (KLB) setiap tahunnya. Perubahan iklim dapat berpengaruh terhadap pola penyebaran dan meningkatkan resiko penularan DBD. Tujuan penelitian adalah untuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 1 publication
0
0
1
4
Order By: Relevance
“…Based on the results of statistical tests, the obtained p-value was 0.331 (p > 0.05), signifying that there is no significant relationship between knowledge and the incidence of dengue fever within the working area of Puskesmas Panongan in Tangerang, Banten. These results do not align with a study conducted by Putri et al (2023b), which reported a relationship between knowledge and the incidence of dengue fever within the working area of Puskesmas Sukarame in Bandar Lampung, with a pvalue of 0.037. In that study, respondents with a low level of knowledge had a 2 times higher chance of contracting dengue fever compared to respondents with a high level of knowledge (OR = 2.586).…”
Section: Knowledge About Dengue Hemorrhagic Fevercontrasting
confidence: 98%
“…Based on the results of statistical tests, the obtained p-value was 0.331 (p > 0.05), signifying that there is no significant relationship between knowledge and the incidence of dengue fever within the working area of Puskesmas Panongan in Tangerang, Banten. These results do not align with a study conducted by Putri et al (2023b), which reported a relationship between knowledge and the incidence of dengue fever within the working area of Puskesmas Sukarame in Bandar Lampung, with a pvalue of 0.037. In that study, respondents with a low level of knowledge had a 2 times higher chance of contracting dengue fever compared to respondents with a high level of knowledge (OR = 2.586).…”
Section: Knowledge About Dengue Hemorrhagic Fevercontrasting
confidence: 98%
“…Berbeda dengan kondisi kelembapan di Kabupaten Bogor memiliki rata-rata 85,99% di mana kisaran tersebut dapat memperpanjang umur nyamuk dan meningkatkan penyebaran virus. Sejalan dengan penelitian (34) menunjukkan tidak ada hubungan yang signifikan pada variabel kelembapan dengan kejadian DBD di Kota Bandar Lampung pada tahun 2016-2018 dengan p value yaitu 0,201 dan nilai (r) yaitu 0,216.…”
Section: Pembahasanunclassified
“…Berdasarkan data yang diperoleh dari Open Data Jakarta, jumlah kasus DBD di setiap Kota Administrasi Jakarta tahun 2018-2020 terlampir pada Gambar 1. menyebabkan replikasi dan penyebaran virus di dalam tubuh nyamuk lebih efektif (Putri et al, 2020). Selain itu, dengan suhu sekitar 22-28 o C membuat persentase keberhasilan penetasan telur nyamuk sekitar 90% dan mengalami penurunan persentase jika tidak pada kisaran suhu tersebut (Yahya, Ritawati dan Rahmiati, 2019).…”
Section: Hasil Data Kasus Dbd DI Kota Administrasi Jakarta Tahun 2018...unclassified